ANALISIS PEMBAGIAN PERAN GENDER PADA KELUARGA PETANI - Herien Puspitawati; Sri Andriyani Fahmi (Jurnal Ilmu Keluarga dan Konsumen, 2008)
The aims of this study were to analyze the gender roles within families, both domestic and farming system activities. The study was conducted at Hambaro Village, Sub-District of Nanggung, Bogor in April to August 2008, by using a cross sectional study design. The location of study was chosen purposively. Based on the correlation analysis, it has been found that the fewer the numbers of family members, the younger the husband’s age, the higher the husband’s education, the older the children under five years old, the higher the numbers of children under five years old, the higher the income and expenditure per capita, the higher the frequencies of planning of the family, and the higher the degree of family problems tend to have the better gender partnerships/ relations between husband and wife in the family domestic activities. Based on the regression analysis, it has been known that family income per capita, frequencies of family planning, and family problems could affect the better gender partnerships between husband and wife in domestic activities. Consistently, numbers of family members, frequencies of family planning, and family problems could affect the better gender partnerships between husband and wife in family farming system activities.